2023
DOI: 10.1007/s12208-023-00385-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of social marketing in achieving the planet sustainable development goals (SDGs)

Abstract: Changing the way citizens behave toward sustainability is essential to achieve the SDGs. Citizens can help create a more prosperous planet for future generations by making sustainable decisions and engaging in environmentally friendly behaviors. This position paper draws attention to how social marketing can encourage pro-environmental behavior conducive to achieving the environmental Sustainable Development Goals (SDGs) set by the United Nations (UN) as part of the 2030 Agenda. The paper also offers critical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…It is a seemingly relatively overlooked line of research and publications even though it subsumes clear results. Rodriguez-Sanchez (2023) presents evidence that social marketing, if properly applied, can be an effective tool for sustainability transformations, and that this potential can be further boosted if combined with use of persuasive technologies such as video, games, and virtual reality tools, and Bogueva et al (2017) describe how social marketing can help stimulate significant diet change away from beef, for example. Yet, in line with the undercutting reference with which Newell et al end their analysis, it is often discussed in non-committal if not subtly critical manner by communications scholars.…”
Section: Social Science Tendencies and Gapsmentioning
confidence: 99%
“…It is a seemingly relatively overlooked line of research and publications even though it subsumes clear results. Rodriguez-Sanchez (2023) presents evidence that social marketing, if properly applied, can be an effective tool for sustainability transformations, and that this potential can be further boosted if combined with use of persuasive technologies such as video, games, and virtual reality tools, and Bogueva et al (2017) describe how social marketing can help stimulate significant diet change away from beef, for example. Yet, in line with the undercutting reference with which Newell et al end their analysis, it is often discussed in non-committal if not subtly critical manner by communications scholars.…”
Section: Social Science Tendencies and Gapsmentioning
confidence: 99%
“…But would that also include democratic control over media systems, even if structured on the basis of the best available knowledge about deep and meaningful participation in decision making (Atlee, 2012; Chilvers, 2008; Macnaghten et al, 2014; Weymouth & Hartz-Karp, 2015)? In such conditions, might there not be a role for social marketing, too (Bogueva et al, 2017; Rodriguez-Sanchez, 2023)? Social marketing has been shown to be very effective in changing imaginaries and behavior to better reconcile sustainable development goals and planetary boundaries (ibid.).…”
Section: Inescapability Of Political Choices and Influencementioning
confidence: 99%